A strategy to improve the work-hardening behavior of Ti–6Al–4V parts produced by additive manufacturing. Issue 3 (4th May 2017) - de Formanoir, Charlotte; Brulard, Alice; Vivès, Solange; Martin, Guilhem; Prima, Frédéric; Michotte, Sébastien; Rivière, Edouard; Dolimont, Adrien; Godet, Stéphane
ABSTRACT: To improve the mechanical properties of additively manufactured parts, specific heat treatments must be developed. Annealing of electron beam-melted Ti–6Al–4V was performed at sub-transus temperatures and followed by water quenching. Such treatments generate an α + α ′ dual-phase microstructure. Microstructural and mechanical characterizations revealed that the heat-treated specimens show a broad range of tensile properties, depending on the fraction of martensite. The specimens treated between 850°C and 920°C exhibit an increase in strength and ductility, which is related to a remarkable hardening behavior. Work-hardening is attributed to kinematic hardening arising from the mechanical contrast between the α and α ′ phases. GRAPHICAL ABSTRACT: IMPACT STATEMENT Innovative heat treatments leading to α + α ′ dual-phase microstructures are developed on Ti–6Al–4V parts produced by additive manufacturing. They lead to unprecedented work-hardening capabilities for this alloy.